2014
DOI: 10.1111/add.12440
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance treatment for opioid dependence with slow‐release oral morphine: a randomized cross‐over, non‐inferiority study versus methadone

Abstract: AimsTo compare the efficacy of slow-release oral morphine (SROM) and methadone as maintenance medication for opioid dependence in patients previously treated with methadone.DesignProspective, multiple-dose, open label, randomized, non-inferiority, cross-over study over two 11-week periods. Methadone treatment was switched to SROM with flexible dosing and vice versa according to period and sequence of treatment.SettingFourteen out-patient addiction treatment centres in Switzerland and Germany.ParticipantsAdults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 38 publications
3
68
2
Order By: Relevance
“…For study inclusion, patients had to be opioid dependent (F11.2 according to ICD-10), aged 18 years or older and already participating in methadone maintenance treatment for at least 26 weeks. The study design is described in detail elsewhere [see [8]]. The main part of the study comprised two crossover periods of 11 weeks each (1 week adjustment phase followed by 10 weeks of treatment; see fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For study inclusion, patients had to be opioid dependent (F11.2 according to ICD-10), aged 18 years or older and already participating in methadone maintenance treatment for at least 26 weeks. The study design is described in detail elsewhere [see [8]]. The main part of the study comprised two crossover periods of 11 weeks each (1 week adjustment phase followed by 10 weeks of treatment; see fig.…”
Section: Methodsmentioning
confidence: 99%
“…To increase the validity of the study results, stringent criteria for the per protocol (PP) population were set to include patients who completed each of the two crossover treatment periods (11 weeks) within a specified time frame of ≥70 days and ≤84 days, who had urinalyses for ≥9 out of 11 weeks per crossover period and no discontinuation of study medication for more than 5 consecutive days [see [8]].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…59 Since this review, an international multisite randomized cross-over trial found that slow-release oral morphine was as effective as methadone in reducing illicit opioid use and retaining individuals in treatment, 60 and superior to methadone for overall patient satisfaction, and reducing cravings and symptoms of dysthymia. [61][62][63] However, because of the small number of trials comparing slowrelease oral morphine to other opioid agonist treatments, slowrelease oral morphine should generally be considered only for use in patients who are intolerant to or have not responded to first-and second-line opioid agonist treatment, and who remain at high risk of opioid-related harms, including overdose death.…”
Section: In Patients For Whom First-and Second-line Treatment Optionsmentioning
confidence: 99%